Authentic Custom and Its Applications in Matters of Marriage in The Kurdistan Region - Yunus Saeed Hussein (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The message of Islam came to all the peoples of the earth, regardless of their races, ethnicities, temperaments and cultures. Therefore, its teachings were characterized by flexibility and facilitation. This is evident in the Sharia’s consideration of custom, which is nothing but the habits of people and their customs settled in the souls and accepted by peaceful minds and temperaments. One of the most common jurisprudential chapters in which custom appears and conflicts to influence the legal ruling is the section on personal status. These issues are affected by the restrictions of social customs and traditions, especially in areas where tribalism and tribalism are still dominant and influential, such as the Kurdistan region. In these circumstances and conditions, customs are common among people and are strengthened by social traditions, so is this a recognized custom in Sharia? Or are there rules and conditions for considering custom and thus building judgments on it from permissible, forbidden, correct and corrupt? After researching some of the personal status issues that are affected by the prevailing custom in Kurdistan, it became clear to me that the custom in some of them is valid and legally considered custom, such as the testimony of an unknown status. In order to fulfill the conditions for correct custom in it, in exchange for matters in which the custom was corrupt and is not recognized as an indefinite testimony regarding Islam for violating the custom of the Sharia ruling based on significant legal evidence.